In the name of the Father, Job’s name. The role of interpellation in practices of subjection - Nogara Notarianni, Bianca (Dialegesthai, 2021)
1. Words in the storm "And yet you have said, "What does God know? Can he judge through the dark cloud? The clouds, to him, are an impenetrable veil,…